Modernizing peasant societies : a comparative study in Asia and Africa - Hunter, Guy.; Institute of Race Relations (London ; New York : Published for the Institute of Race Relations [by] Oxford University Press, 1969)
This book is the outcome of two and a half years' work on a project sponsored jointly by the Institute of Race Relations and the Overseas Development Institute and financed by a grant from the Ford Foundation. The purpose of the project was to inquire more deeply into the effect of 'the transfer of institutions from developed to developing countries'.
Includes bibliographical references and index.
rpm 24/01/2019
Loans
Keywords: Agriculture; Developing countries